The Leadership Competency in Vietnam Public Administration - Lan, Mai Thanh; Hung, Ta Huy (Organizations and Markets in Emerging Economies, 2018)
Globalization and technological development have changed people’s demand, which leads to many challenges for public and private sectors. Public administration can overcome the challenges by reforming their structure and performance. In this research, the authors affirmed the important roles of leaders in public administration. This research used the integrated leadership theory in the context of Vietnam public administration to build a framework of competency for leaders. The Key Informant Panel and the in-depth interview method were implemented to achieve the research objectives. Research findings have built a leadership competency framework for the public sector, which benefits both researchers and practioners. For researchers, the findings can add to leadership competency theories, especially in the public sector. For policy-makers, the findings can be solid foundations which they can rely on to work out policies for leadership development in Vietnam public sector.